The development of professional management
1 online resource.
Keywords: "This shortform book presents key peer-reviewed research selected by expert series editors and contextualised by new analysis from each author on the development of professional management. With contributions on consultancy and training consultants, Taylorism and its appeal to socialists, the social position of managers, and the growth of the managerial class. Of interest to business and economic historians, this shortform book also provides analysis and illustrative case-studies that will be valuable reading across the social sciences"--